2016
DOI: 10.17795/iji-35691
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Dexell Endoscopic Treatment of Vesicoureteral Reflux: An Option for the Management of Recurrent Urinary Tract Infection

Abstract: Background: Recurrent urinary tract infection (UTI) due to vesicoureteral reflux (VUR) is common in Iraq. Endoscopic treatment of VUR is used with advantages over antibiotic prophylaxis and ureteral reimplantation. Objectives: This study was performed to assess the efficacy of a new agent, Dexell, for treating patients with VUR and its ability to manage recurrent UTI. Materials and Methods:This research was a prospective study recruiting 156 patients with VUR treated by endoscopic subureteric injection of Dexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…However, recent data, including this study, have shown that endoscopic corrections for grade V have a higher success rate than open-surgery, with only 3.6% failure rate and 5.4% recurrence rate (26). In a previous study conducted in Iraq, de novo contralateral VUR was found in 3.8% of the patients after operation (27). Additionally, Kirsch et al similarly reported 4.5% occurrence of contralateral VUR after the operation (28).…”
Section: Discussionmentioning
confidence: 50%
“…However, recent data, including this study, have shown that endoscopic corrections for grade V have a higher success rate than open-surgery, with only 3.6% failure rate and 5.4% recurrence rate (26). In a previous study conducted in Iraq, de novo contralateral VUR was found in 3.8% of the patients after operation (27). Additionally, Kirsch et al similarly reported 4.5% occurrence of contralateral VUR after the operation (28).…”
Section: Discussionmentioning
confidence: 50%
“…However, recent data, including this study, have shown that endoscopic corrections for grade V have a higher success rate than open-surgery, with only 3.6% failure rate and 5.4% recurrence rate (26). In a previous study conducted in Iraq, de novo contralateral VUR was found in 3.8% of the patients after operation (27). Additionally, Kirsch et al similarly reported 4.5% occurrence of contralateral VUR after the operation (28).…”
Section: Discussionmentioning
confidence: 59%
“…VUR was common in our study, and after correcting it, UTI occurred in 5.9% of the recruited participants. In a previous study conducted in Iraq and after successful correction of VUR, recurrent UTI was eliminated in all participants (27). Thus, screening for VUR should be offered to all patients presenting with recurrent UTI.…”
Section: Discussionmentioning
confidence: 98%
“…Approximately, %50 of women will develop UTIs once in their life time and between 20% to 40% of them experience recurrent episodes of UTIs, Whilst 20% of UTI cases are men [8]. Treatment of UTIs varies according to age , sex , underlying disease , infective organism and involvement of upper or lower urinary tract [9,10].…”
Section: Introductionmentioning
confidence: 99%